Systematic analysis of the role and significance of target genes of active ingredients of traditional Chinese medicine injections in the progression and immune microenvironment of hepatocellular carcinoma - Wang, Chao; Yang, Lili; Xu, Shaoheng; Guo, Hui; Guan, Hewen; Wang, Qiannan; Jiang, Xueyan; Fei, Mingyang; Zhang, Jinbao (Frontiers in Pharmacology, 2023)
Background: Traditional Chinese medicine in China is an important adjuvant therapy for the treatment of hepatocellular carcinoma(HCC) and traditional Chinese medicines injections have a wide range of clinical applications. The purpose of this study was to identify the active ingredients and related genes of traditional Chinese medicine injections that can treat hepatocellular carcinoma. Methods: Effective small molecule components were extracted from 14 types of traditional Chinese medicines from 8 injections and the main gene targets were identified. The 968 patients with HCC were classified based on the target gene set, and the characteristics of patients with different subtypes were analyzed. Patients with two subtypes of HCC were compared with normal tissues and cirrhosis to identify important gene targets related to traditional Chinese medicines in HCC progression. Results: In this study, 138 important genes associated with traditional Chinese medicines were identified and two HCC subtypes were identified. By analyzing the differences between the two subtypes, 25 related genes were associated with HCC subtypes. Through clinical and pharmacological analysis, this study identified quercetin as an important traditional Chinese medicines small molecule and secreted phosphoprotein 1 (SPP1) as an important oncogene in HCC. Conclusion: Traditional Chinese medicines injection is an important adjuvant treatment modality for HCC. SPP1 is an important oncogene in HCC.